PARENTING CRAFTSMEN BAMBOO IN EDUCATION CHILDREN - Aini Nur Faizah; Imania Najmuna (IKIP Siliwangi, 2019)
This study aims to determine the parenting pattern of bamboo craftsmen in educating children by focusing on the parenting patterns of bamboo craftsmen in educating children, the factors that determine the parenting patterns of bamboo craftsmen in educating children and the efforts of parents of bamboo craftsmen in improving children's education. This research uses qualitative research type. The data collection procedure is by observation method, interview method, and documentation method. The research findings show that the parenting pattern of bamboo craftsmen is by authoritative or democratic parenting type. Factors that determine parenting are influenced by the characteristics of family structure, parent profession, parent competence, characteristic of child structure and interaction between parent and child. Efforts made by parents of bamboo craftsmen in improving children's education that is by staying beside children, accompanying children when learning and give sympathy to their children. In addition, giving love to children by giving rewards to children when the child managed to do something.